Supply Chain Coordination with Quantity Discount for Seasonal Demand - Mikhail M Sher; Seung-Lae Kim (International Journal of Supply Chain Management, 2014)
Coordination between manufacturers and multiple buyers represents an important problem in supply chain management. In this paper, we develop a supply chain coordination mechanism in a system with a dominant manufacturer that delivers seasonal products to a group of buyers. These buyers have common replenishment times and receive delivery through a common delivery channel. A twice-stage ordering and production system is introduced in which the first order is placed at some time in advance of the selling season and a second order is placed closer to the selling period. This reorder strategy allows the buyer to collect additional information about seasonal demand, thereby reducing demand forecast error and simultaneously smoothing out production time. This twice-stage model results in savings for both manufacturer and the buyers. Strategies for developing sustainable cooperation between manufacturers and buyers are discussed in light of the conclusions of this model.